Pendampingan Dan Pembuatan Media Pembelajaran Interaktif Di SDN 1 Montong Tangi - Faruq, Faruq Huaidi; Donna Boedi Maritasari; Helmalia Maya Rosanti; Baiq Lu’luil Maknun; Arini Safitri; Era Andini; Siti Aisyah; Khairur Rosid Mahendra; Zaenul Amrullah; Rifky Eka Saputra; Zahrul Irfan; Humaidi (Universitas Hamzanwadi, 2025)
The use of learning media that utilize technology is very important in this era so that interesting and effective learning media such as learning media in the form of visual, audio, and audiovisual are needed. One form of audiovisual media that is very helpful is video, which can invite students to think more concretely and logically and create an imaginative, creative, and memorable learning experience. Assistancein the creation of interactive-based learning media using Adobe Animate for 5th grade teachers of PPKn subjects at SDN 1 Montong Tangi as a form of effort to implement this. The purpose of this mentoring is to improve teachers' skills in utilizing technology to create interesting and interactive learning media, in order to support an effective and innovative learning process. The method used in this activity is a hands-on training approach, focusing on the introduction and use of Adobe Animate features, as well as its application in creating learning media that are in accordance with PPKn materials. It can be concluded that this service project is suitable for teachers and students, this is expected to increase student motivation, participation in learning, and contribute to the use of technology in the world of education, especially at the elementary level